Bud, Not Buddy - Curtis, Christopher Paul (New York : Delacorte Press, 1999)
Summary: Ten-year old Bud, a motherless boy living in Flint, Michigan during the Great Depression, escapes a bad foster home and sets out in search of the man he believes to be his father--the renown bandleader, H. E. Calloway of Grand Rapids.
Keywords: Runaways -- Fiction; Afro-Americans -- Fiction